Socialization of The Use of Sisik Naga Leaves (Drymoglossum Piloselloides) Medicinal Plant as An Antibacterial for The Lubuk Pakam Pekan - Pranata, Chandra; Wiratma, Dicky Yuswardi; Santika, Rimma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
In Indonesia, one type of plant that is often found is Drymogglossum Piloselloides, or better known as dragon scale leaves. These leaves are included in the category of herbal plants or traditional medicines which are rich in anti-inflammatory, anti-oxidant and anti-cancer compounds. Not only this, secondary metabolite compounds contain various other forms, namely flavonoids, tannins and saponins, which are believed to be antibacterial, to inhibit the growth of bacteria that cause acne, including Staphylococcus epidermidis, which is a member of the genus Gram-positive staphylococcus. In this community service activity, the aim is to provide information about the role and benefits of dragon scale leaves which can be an antibacterial agent for the wider community. In the service program carried out through socialization media using lecture, question and answer and implantation methods with the participation of 15 people in Lubuk Pakam. In accordance with the PkM program that has been produced, a conclusion was obtained regarding wider community insight and knowledge about dragon scale leaves which can be used for antibacterial purposes, in this case proven by the increase in the posttest score which was compared with the pretest score. The average increase in knowledge of PkM participants was obtained with a value of 28.4. Not only that, the maximum posttest score was obtained with a score of 85, in contrast to the lowest posttest score, namely 55 if a comparison was made with the pretest that had been carried out previously.